O conceito de subjetividade em A Ideia da Fenomenologia - Souto, Andressa Alves (2014)
The objective of this research is the study of the concept of subjectivity as such it develops in lessons on The Idea of Phenomenology (1907), by Edmund Husserl. Such concept in this work is linked to a critique of the traditional conception of representation, according to which the psychic immanence designate one intramental ontological region in which they find representations as substitutes for reference objects. To the extent that this criticism is made, the relationship between immanence and transcendence are redefined, providing a new phenomenological concept of subjectivity. This, in turn, is founded on the idea of authentic immanence, which includes not only sensations and acts (real [reell] immanence), but intentional objects in their modes of appearance (intentional immanence). This conception of subjectivity signals a change in relation to what had been advocated in the work initiating the Husserlian phenomenology - the Logical Investigations (1900-1). At this, subjectivity is presented as containing only the noetic character of knowledge - the real immanence -, while in the work studied here it also includes what subsequently one designate, in phenomenology, as noematic character of knowledge the immanence in intentional sense. The hypothesis of reading proposed here is that this conception of subjectivity is made possible by analysis of Husserl on time-consciousness, from 1905, in which it reveals that even within the "flow" of experiences, there is something identical, which beyond the scope of real immanence. This recognition would have led Husserl to the conception that the limitation of subjectivity to the sphere of real immanence is founded on a mistaken association between the latter and immediate evidence. Therefore, the route of Husserl's text in The Idea of Phenomenology will moves itself around the dissociation between these two notions. Draw will be, therefore, the path taken by Husserl in this work in order to highlight the notion of subjectivity that emerges in it.